2022
DOI: 10.1200/jco.2022.40.16_suppl.5598
|View full text |Cite
|
Sign up to set email alerts
|

Stage 1 results of BrUOG 354: A randomized phase II trial of nivolumab alone or in combination with ipilimumab for people with ovarian and other extra-renal clear cell carcinomas (NCT03355976).

Abstract: 5598 Background: Clear Cell Carcinoma (CCC) outside the kidney is a rare tumor that can arise from multiple organs, including the ovary, endometrium and cervix. Extra-renal CCC is chemoresistant and has a poor prognosis. Data suggest that CCC of the gynecologic tract resembles the genomic profile of Renal Cell Carcinoma (RCC), which is responsive to immune checkpoint inhibition (ICI) therapy. We are conducting a two-stage phase 2 trial evaluating immunotherapy for extra-renal CCC. The primary objective is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…49 BrUOG 354 explored the activity of the PD-1 inhibitor nivolumab with and without ipilimumab (anti-CTLA4) in ovarian or extra-renal clear-cell pathologies; the stage 1 results of this study reported an overall response rate of 26.6% ( n = 4/15) in the combination arm compared to 16.7% ( n = 2/12) for nivolumab alone and so stage 2 will focus on dual treatment with nivolumab and ipilimumab. 50 In comparison to these two studies, MOCCA was a phase II study exploring the role of the PD-L1 inhibitor durvalumab against physicians choice of chemotherapy; this study was negative with an overall response rate to durvalumab of 10.7% and no significant difference in OS. 51 INOVA is a phase II study that is currently exploring the use of sintilimab (anti-PD1) in combination with bevacizumab in the treatment of recurrent CCOC; although this trial is still ongoing, preliminary results following the recruitment of 20 evaluable patients (out of a planned accrual of 38) have reported an overall response rate of 40%.…”
Section: Clear-cell Ovarian Cancermentioning
confidence: 99%
“…49 BrUOG 354 explored the activity of the PD-1 inhibitor nivolumab with and without ipilimumab (anti-CTLA4) in ovarian or extra-renal clear-cell pathologies; the stage 1 results of this study reported an overall response rate of 26.6% ( n = 4/15) in the combination arm compared to 16.7% ( n = 2/12) for nivolumab alone and so stage 2 will focus on dual treatment with nivolumab and ipilimumab. 50 In comparison to these two studies, MOCCA was a phase II study exploring the role of the PD-L1 inhibitor durvalumab against physicians choice of chemotherapy; this study was negative with an overall response rate to durvalumab of 10.7% and no significant difference in OS. 51 INOVA is a phase II study that is currently exploring the use of sintilimab (anti-PD1) in combination with bevacizumab in the treatment of recurrent CCOC; although this trial is still ongoing, preliminary results following the recruitment of 20 evaluable patients (out of a planned accrual of 38) have reported an overall response rate of 40%.…”
Section: Clear-cell Ovarian Cancermentioning
confidence: 99%